Implementation of Organic Waste Shredder Technology to Reduce Waste Volume and Enhance Economic Value in Randakari Village, Cilegon - Sari, Putri Dina; Sholihin, Miftahus; Ikhsan, Aulia; Kuraysia, Fera; Aprizkiyandari, Siti; Delano, Muhammad Fabian Reinhard; Ramadhan, Ilham (Journal of Community Service in Science and Engineering (JoCSE), 2026)
Household organic waste management remains a primary challenge in urban areas and industrial buffer zones, including Randakari Village, Ciwandan District, Cilegon City. The accumulation of food scraps and inadequate waste management facilities often trigger the emergence of disease vectors and unpleasant odors in residential areas. This community service program aims to reduce the volume of organic waste while creating economic value through the introduction of appropriate technology, specifically an organic waste shredder. The implementation method consisted of socialization, technology design, direct training (machine operation demonstration), and evaluation involving university students, village officials, and local residents over a one-month period. Results indicate that this low-power machine (200 Watts) effectively broke the waste accumulation chain with an optimal capacity of 5 kilograms per cycle. The shredded waste was subsequently converted into liquid organic fertilizer (LOF) using a layering system inside used water gallons, enriched with rice-washing water. This process yielded an average of 700 mL to 1 liter of LOF per cycle. The program's implementation has gradually reduced local waste volumes while simultaneously enhancing the ecological awareness and technical skills of the residents. For long-term sustainability, the community is now capable of operating the equipment independently and replicating the fertilizer production, which opens up future commercialization opportunities for processed waste products.